Effects of Transcranial Direct Current Stimulation Block Remifentanil-Induced Hyperalgesia: A Randomized, Double-Blind Clinical Trial - Braulio, Gilberto; Passos, Savio C.; Leite, Fabricio; Schwertner, Andre; Stefani, Luciana C.; Palmer, Ana C. S.; Torres, Iraci L. S.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Pharmacology, 2018)
Background: Remifentanil-induced hyperalgesia (r-IH) involves an imbalance in the inhibitory and excitatory systems. We tested the hypothesis that transcranial Direct Current Stimulation (t-DCS), given its analgesics effects, could prevent r-IH. The primary outcomes included the Numerical Pain Score NPS (0-10) during the repetitive cold test (rCOLDT) and the change on the NPS (0-10) during the conditioned pain modulation (CPM)-task. The secondary outcomes were the heat pain threshold (HPT) and the reaction-time during the Ice-Water Pain Test (IPT). Methods: This double blinded, explanatory factorial randomized trial included 48 healthy males, ages ranging 19 to 40 years. They were randomized into four equal groups: active (a)-tDCS/saline, sham (s)-tDCS/saline, a-tDCS/remifentanil and s-tDCS/remifentanil. We applied tDCS over the primary motor-cortex. Results: During the rCOLDT, there was a significant group effect on the cumulative NPS scores (P=0.01). The s-tDCS/remifentanil group presented larger pain scores during rCOLDT, [mean (SD) 5.49 (1.04)] and a-tDCS/remifentanil group had relative lower pain scores [4.15 (1.62)]; showing its blocking effect on r-IH. a-tDCS/saline and s-tDCS/saline groups showed lowest pain scores during rCOLDT, [3.11(1.2)] and [3.15(1.62)], respectively. Remifentanil groups showed positive scores in the NPS (0-10) during the CPM-task, that is, it produced a disengagement of the descending pain modulatory system (DPMS). Also, s-tDCS/Remifentanil compared to a-tDCS showed lower HPT and larger reaction-time during the IPT. Conclusion: These findings suggest that effects of a-tDCS prevents the summation response induced by r-IH during rCOLDT and the disengagement of DPMS.